Debunking the Myth of the Endogenous Antiangiogenic Vegfaxxxb Transcripts. (June 2020) - Dardente, Hugues; English, William R.; Valluru, Manoj K.; Kanthou, Chryso; Simpson, David
Abstract : In this opinion article we critically assess evidence for the existence of a family of antiangiogenic vascular endothelial growth factor ( Vegfaxxxb ) transcripts, arising from the use of a phylogenetically conserved alternative distal splice site within exon 8 of the VEGFA gene. We explain that prior evidence for Vegfaxxxb transcripts in tissues rests heavily upon flawed RT-PCR methodologies, with the extensive use of 5′-tailing in primer design being the main issue. Furthermore, our analysis of large RNA-seq data sets (human and ovine) fails to identify a single Vegfaxxxb transcript. Therefore, we challenge the very existence of Vegfaxxxb transcripts, which further questions the physiological relevance of studies based on the use of 'anti-VEGFAxxxb' antibodies. Our analysis has implications for the proposed therapeutic use of isoform-specific anti-VEGFA strategies for treating cancer and retinopathies. Highlights: Following identification of an alternative splicing event that creates a family of transcripts encoding antiangiogenic isoforms of VEGFA, modulation of splice site selection was heralded as an opportunity to regulate angiogenesis in the clinical setting. The discovery of major flaws in the RT-PCR methodology used in the seminal identification of Vegfaxxxb transcripts in 2002 and subsequent studies cast doubt upon their very existence. The lack of any reads supporting the putative Vegfaxxxb splice events in multiple large-scale and publicly available RNA-seq data sets also indicates that Vegfaxxxb transcripts are not expressed endogenously. The absence of Vegfaxxxb mRNA implies that the antibody-based detection of VEGFAxxxb proteins reported by many studies is an artefact. A model of overall angiogenic potential based upon the balance between classical angiogenic VEGFAxxx and antiangiogenic VEGFAxxxb isoforms is not supported by robust experimental evidence and, therefore, the development of clinical applications based on this model is questionable.